Blue Economy dan Hak Ulayat Laut di Indonesia: Sinergi untuk Kelestarian Laut dan Kesejahteraan Masyarakat - Wiwin Yulianingsih (Jurnal Hukum Lex Generalis, 2025)
Indonesia's maritime natural resources are one of the biggest assets that support the country's economic life and ecosystem. In this context, the blue economy and customary maritime rights are two concepts that protect maritime natural resources. The blue economy offers a sustainable approach to maritime resource utilisation, while customary maritime rights recognise the rights of indigenous communities to manage their maritime areas in a traditional and sustainable manner. This article discusses the linkages between the blue economy, customary maritime rights and the protection of maritime natural resources in Indonesia, and how their integration can provide solutions for the sustainability of maritime resources.